BACTERIOLOGICAL ANALYSIS AND ITS ANTIBIOGRAM PROFILE OF PHARYNGITIS CASES FROM THE PATIENTS ATTENDING REFERRAL HOSPITAL, SIKKIM, INDIA - Moirangthem, and, A; Gurung, K (BALI MEDICAL JOURNAL; Volume 2 Number 1, January-April 2013, 2013)
Objective: Infections of throat have a tremendous impact on public health. This present study aims to find out the bacterial load in throat infections as well as their susceptibility pattern in patients attending Central Referral Hospital, Tadong, Sikkim. Method : A total of 55 symptomatic patients having throat infections attended Central Referral Hospital Sikkim, among which 28 were males and 27 were females. A total of 55 throat swabs were collected from the patients with symptoms of pharyngitis. Results : Out of 55 samples, culture was positive in 37 samples. Twenty one strains of Staphylococcus aureus , 13 strains of Streptococcus pyogenes, 1 strain of Pseudomonas aeruginosa and 2 strains of Proteus spp . were isolated. The isolation rate of Staph.aureus was found to be statistically significant when compared between the isolation rate of Ps.aeruginosa , Stp. pyogenes and Proteus spp . 3 isolates of Staph. aureus were sensitive to penicillin, 1 isolate was moderately sensitive and 17 isolates were resistant. 12 strains of Staph.aureus were sensitive to methicillin. Methicillin resistant was seen in 9 strains of Staph. aureus . The strains of Stp. pyogenes isolated were either moderately sensitive or resistant to the used antibiotics, it was not sensitive to any of the used antibiotics. It was moderately sensitive to amoxiclave, clarithromycin, erythromycin and resistant to clindamycin and cefuroxime. 100% strains of Ps. aeruginosa were resistant to ciprofloxacin, gentamicin, piperacillin, ticarcillin, tobramycin and the strains were sensitive only to imipenem (100%). Further 100% strains of Proteus spp .were sensitive to cefuroxime, azithromycin, amoxicillin and cephalexin. Conclusion: Our study showed a high rate of monomicrobial infection. The control of throat infections demands the availability of primary care and appropriate treatment.
Keywords: Pharyngitis, Staphylococcus aureus, Streptococcus pyogenes, Pseudomonas aeruginosa, Proteus spp.